2010
DOI: 10.1111/j.1600-051x.2010.01604.x
|View full text |Cite
|
Sign up to set email alerts
|

Sense of coherence and oral health in dentate adults: findings from the Finnish Health 2000 survey

Abstract: SOC is positively associated with various aspects of adult oral health, in part because of the better oral health-related behaviours among people with a strong SOC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 43 publications
5
68
1
1
Order By: Relevance
“…12,14,15,18,20 Therefore, this study provides information from a group with different characteristics, thus allowing comparisons with the SOC of a population presenting other cultural and behavioral values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,14,15,18,20 Therefore, this study provides information from a group with different characteristics, thus allowing comparisons with the SOC of a population presenting other cultural and behavioral values.…”
Section: Discussionmentioning
confidence: 99%
“…Freire et al 5 found an association between SOC and cavities in the posterior teeth of adolescents, a result that was not confirmed by multivariate analysis. 5 When evaluating the relationship between the SOC and clinical oral health outcomes in adults, Bernabé et al 20 found that a higher SOC was associated with fewer cavities and fewer missing teeth, after adjusting for social, demographic and behavioral variables. The results of this study indicate that a higher SOC can contribute to a better oral health condition of adults and the elderly, observing also that the social and demographic factors had no influence on this result, thus confirming what was found in the study by Bernabé et al 20 The lack of influence of socioeconomic status on the relationship between SOC and oral health behaviors in adults has been observed in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the points where the SOC has relevance in oral health is in its relationship with healthy behaviors because SOC could influence both the origin and recovery from diseases through effective coping by the avoidance of unhealthy behaviors and acquisition of behaviors that promote healthy habits. Particularly, Bernabé et al reported a strong relationship between SOC and the number of decayed teeth in older adults, which decreased by 0.2 teeth for each unit that increased in the SOC scale 26 .…”
Section: Dental Cariesmentioning
confidence: 99%
“…Developed by Antonovsky in the 70s, SOC is a variable that could facilitate the successful coping with stressful situations and also achieving the development and subsequent maintenance of health. This is defined as "a global orientation that expresses the extent to which the individual has a durable and dynamic sense of confidence, characterized by a high probability of predicting the internal and external environments" 26 . One of the points where the SOC has relevance in oral health is in its relationship with healthy behaviors because SOC could influence both the origin and recovery from diseases through effective coping by the avoidance of unhealthy behaviors and acquisition of behaviors that promote healthy habits.…”
Section: Dental Cariesmentioning
confidence: 99%